Knowledge, Behavior, and Role of Health Cadres in The Early Detection of New Tuberculosis Case in Wonogiri (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Tuberculosis (TB) is an infectious disease that remain a serious health problem. Seventy five percent of TB cases in developing countries are found in people of productive age. Delay in case finding and handling will lead to disability and death and hamper TB control program. The objective of this study was to evaluate how far the role of health cadres in detecting new case of TB in Tirtomoyo, Wonogiri. The study design was a cross-sectional and data was collected from February to April 2019. The population of the study was all health cadres in Tirtomoyo numbering 465 cadres from 9 villages. Sample of the study was the cadres in Tirtomoyo who met inclusion criteria set by the researchers with total number of 202 cadres. The sampling technique was purposive sampling, and the inclusion criteria included: active person, in a healthy state, not currently receiving inpatient care in hospital, and agree to participate in the study. Subjects completed the questionnaire consisting of sociodemographic data, knowledge, behavior, and the role of cadre. The data was analyzed using SPSS version 22. The behavior of the health cadres was found to significantly correlate to the role of cadres in early detection of new TB cases with p value of 0.039 (OR 0.121– 0.946). The health cadres play an essential role, and active screening for TB detection was more effective than passive screening. Early diagnosis would affect the success of the TB treatment program.